1980
DOI: 10.1007/bf02774312
|View full text |Cite
|
Sign up to set email alerts
|

New device for the measurement of hydrogen clearance rate from the gastric mucosa

Abstract: The hydrogen clearance rate of the nucosa of the glandular stomach of the anesthetized rat was obtained with the platinum electrode in contact with the surface of the gastric mucosa (Contact Electrode Method). By using two indicator electrodes, the gastric blood flow was measured simultaneously with one electrode in contact with the mucosal surface (Contact Electrode Method), and with the other electrode inserted into the gastric wall (Inserted Electrode Method). Pentagastrin produced increase in blood flow by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

1987
1987
1993
1993

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
1
1
Order By: Relevance
“…The resting blood flow in the corpus mucosa was slightly higher than that in the antral mucosa. This is in agreement with previous findings in conscious animals (25,26), whereas in anaesthetized animals it is generally reported that antral blood flow is higher than the corpus blood flow (21)(22)(23)(24).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The resting blood flow in the corpus mucosa was slightly higher than that in the antral mucosa. This is in agreement with previous findings in conscious animals (25,26), whereas in anaesthetized animals it is generally reported that antral blood flow is higher than the corpus blood flow (21)(22)(23)(24).…”
Section: Discussionsupporting
confidence: 93%
“…The basal blood flow values in the stomachs of the conscious rats were higher than those reported in anaesthetized animals (21)(22)(23)(24). The resting blood flow in the corpus mucosa was slightly higher than that in the antral mucosa.…”
Section: Discussioncontrasting
confidence: 72%
“…Using the well-validated hydrogen gas clearance technique in more recent studies, increases in mucosal blood flow were also observed in the rat during stimulation of acid secretion by pentagastrin infusion (Murakami et al, 1982;Leung et al, 1984;Pique et al, 1992a). Furthermore, using both direct visualization of rat submucosal vessels and laser Doppler flowmetry, pentagastrinstimulated acid secretion was associated with an increase in microvascular perfusion, although a direct correlation between these parameters was not observed (Holm-Rutili & Berglindh, 1986).…”
Section: Importance Of the Gastric Microcirculationmentioning
confidence: 99%